PCR-SSCP and Sequencing of CXCR2 Receptor Gene in Vrindavani Cattle - Shivanand, Dige Mahesh; Ahlawat, S.P.S; Bhusan, Bharat; Tiwari, A. K.; Sonawane, Arvind; Kumar, Pushpendra; Inamdar, B.; Dutt, Triveni (Journal of Advanced Veterinary Research, 2011)
Genetic markers associated with inflammatory responses during mastitis could aid in the selection of diseased cattle. One potential marker is CXCR2, a chemokine receptor required for neutrophil migration to infection sites. The objective of this experiment was to identify genetic polymorphism of CXCR2 gene and associate it with subclinical and clinical mastitis. Ninety five Vrindavani crossbred cows (42-mastitis tolerant and 53-clinical mastitis) that completed at least two full lactations were taken for study. Blood of selected crossbred cows was collected, and genomic DNA was isolated by phenol chloroform method. The DNA of good quality having OD ratio (260/280 nm) between 1.7-1.9 were used for further analysis. PCR-SSCP technique was used to reveal the polymorphism in 269bp fragments of CXCR2 gene. The 269 bp fragment of CXCR2 gene was found to be monomorphic in all the DNA samples of crossbred cows.